(untitled) (Scientific journal of the Fergana State University, 2024)
The term sociolinguoculturology and the information about its interconnected fields have been explained in the article. In addition, the scientists opinions who worked in this field were presented. The fact that children’s games are connected with the cultural environment has been shown in the research strategy. Anthropological studies of games are closely related to cultural change, i.e., evolution, diffusion, or survival, and to other aspects of culture, such as child-rearing practices, religion, ritual, recreation, warfare, and ecology have been shown. Also, in the article games were studied from the viewpoint of antiquarianism, evolutionism, diffusionism, functionalism, structuralism. It should be noted that familiarization and playing not only folk games, but also other nations’ games will help children to expand their imagination, at the same time increase their thinking ability, their interest in knowing the world.